Right atrium area is associated with survival after out-of-hospital cardiac arrest: a single-center cohort study - King Hei Dominic Cheng; Samir Sulemane; Sara Fontanella; Petros Nihoyannopoulos (Echo Research and Practice)
Abstract Background Out-of-hospital cardiac arrest (OHCA) is associated with high mortality, highlighting the importance of identifying prognostic factors to guide treatment escalation plans. This study investigates the short-term prognostic potential of transthoracic echocardiogram (TTE), a commonly performed investigation in OHCA patients. This study is among the first to report left ventricle (LV) global longitudinal strain (LVGLS) in OHCA patients. Methods This single-center retrospective cohort study included 54 patients treated between 2019 and 2022, during the COVID-19 pandemic. Patient characteristics were reported using the 2015 Utstein template, and echocardiographic parameters were assessed following British Society of Echocardiography guidelines. Univariate analyses compared TTE parameters by survival-to-discharge and implantable cardioverter-defibrillator implantation outcomes. Correlations between LV ejection fraction (LVEF) derived from cardiac magnetic resonance imaging (cMRI) and echocardiographic LV systolic parameters were evaluated. Results The survival-to-discharge rate was 77.8%. Non-survivors had a significantly larger right atrium (RA) area (RAA) (20.8 cm2 vs. 15.2 cm2 in survivors; p = 0.003). No statistically significant differences were observed for other right or left heart parameters. The median LVGLS was reduced at -11.4% (interquartile range: -14.0 to -7.6). LVEF correlates well on cMRI and TTE (Pearson correlation coefficient = 0.830). Conclusion This study identifies a novel association between larger RAA and short-term mortality following OHCA, alongside a higher survival rate in a tertiary center. Further research should consider incorporating RA parameters into analyses to refine prognostic assessments.